The Impact of Feminist Counseling on Women’s Mental Health in the Digital Era: A Systematic Review. - Alya Nurmaya; Amiruddin Amiruddin (PSDKU Guidance and Counseling, Universitas Negeri Surabaya, 2025)
This study explores the impact of feminist counseling on women’s mental health within the digital era, focusing on its effectiveness in addressing anxiety, depression, and gender-based trauma. Feminist counseling, a client-centered approach rooted in empowerment and structural analysis, has shown significant promise in improving mental health outcomes by helping women understand and navigate the systemic roots of their challenges. Following the PRISMA methodology, this study conducted a systematic literature review using major academic databases, including Scopus and ScienceDirect. The search strategy employed Boolean operators with keywords such as “Feminist Counseling,” AND “Women’s Mental Health,” AND “Digital Era,” AND “Online Counseling,” targeting studies published between 2009 and 2024. Inclusion criteria focused on peer-reviewed articles addressing feminist counseling, mental health, and digital technology, while studies that lacked relevance or methodological rigor were excluded. The results reveal significant benefits of integrating digital tools into feminist counseling, such as improved accessibility for underserved communities and the flexibility to accommodate clients' diverse needs. However, challenges include limited emotional engagement in virtual settings and inequitable access to digital platforms among marginalized populations. This study underscores the need for a more inclusive and technology-driven approach to feminist counseling to ensure its effectiveness and accessibility in the digital age. Recommendations include the development of affordable, secure, and culturally sensitive digital platforms, as well as training programs to help mental health professionals adapt feminist principles to virtual environments. By addressing existing barriers and leveraging technological advancements, feminist counseling can play a transformative role in creating an equitable and supportive mental health care system for women. These findings provide a foundation for future research, policy development, and innovation in feminist mental health interventions.